Promotion of Weather Resilient Technologies, Practices, and Services: Rice (Paddy) Crop - CGIAR Research Program on Climate Change, Agriculture and Food Security; BAIF Development Research Foundation (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Rice is India's dominant crop, contributing 25% to the total cropped area and 45% to the total production of principal crops in the country. It is primarily rain-fed in most parts of the country and majorly cultivated by marginal and small farmers. While crop yields have been increasing, the potential to close the existing yield gap is increasingly challenged by climatic risks, threatening the food security of the population. The present case study shows that improved and resilient practices such as plantation of climate-resilient variety of paddy, Direct Seeding of Rice (DSR), line transplanting nearly doubled the rice production for the farmers associated with the project.